Accountability and Enhancement: Some Religious, Historical and Educational Considerations - Wan Daud, Wan Mohd Nor (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Accountability and Enhancement: Some Religious, Historical and Educational Considerations